Uprising - Nielsen, Jennifer A. (Scholastic Press, 2024)
Twelve-year-old Lidia's life is forever changed by the Nazi occupation of Poland, leading her to join the resistance movement to fight against the Nazis and aid Jewish people in the Warsaw Ghetto during WWII.